Government Communication and the 50-year Dubai Charter - Ribeiro, Diamantino (2021)
Government communication is increasingly one of the most visible aspects of political communication. As part of the longitudinal study that has been carried out since 2016 on the communication of the government of Dubai and the United Arab Emirates, in particular on the Ministry of Happiness, it was considered that the 50-year Charter, as a legacy document of governance, should undoubtedly be part our study. In this paper, the content analysis of the 50-year Charter is performed with the purpose of understanding, on the one hand, the main political concepts contained therein and, on the other, the approach to Happiness and Positivity in that document. In the scope of government communication, we intend to understand the visibility given to publication in the media; to this end, we collected and analysed the headlines of the news published in the latent corpus on the 50-year Charter. The results allow us to conclude that, with regard to the relationship between the content and the National Happiness and Positivity Programme, it is possible to find a close connection, namely through the value of charity as an element capable of creating happiness. As for the visibility of the news in the media, we concluded that there is a cadence of information and that the news goes on over time with emphasis also being given to the implementation of the actions described in the Charter by several organisations.